Causal relationship between schizophrenia and five types of dementia: A bidirectional two-sample Mendelian randomization study - Feng Tao; Shizhe Deng; Bifang Zhuo; Jingyue Liu; Xuan Liang; Jiangwei Shi; Zhihong Meng (PLoS ONE, 2025)
Background Although observational research indicates an association between schizophrenia and dementia, it is unclear whether the two are causally related. In order to examine the causal relationship between schizophrenia and five types of dementia (all-cause dementia, Alzheimer’s disease, vascular dementia, frontotemporal dementia, and dementia with Lewy bodies), we performed a bidirectional two-sample Mendelian randomization analysis. Methods In this study, pooled statistics of schizophrenia and dementia were obtained from the Large-scale genome-wide association study (GWAS) in individuals of European ancestry. Inverse variance weighted (IVW) was the primary statistical approach used in this Mendelian randomization, to further support our findings, we also used MR-Egger, weighted median, and cML-MA. We also used a number of sensitivity analyses to evaluate pleiotropy and heterogeneity. Results In the study of the effect of schizophrenia on dementia, findings from the IVW analysis suggested that schizophrenia is associated with an increased risk of all-cause dementia (OR = 1.065, 95%CI: 1.027 ～ 1.104, P = 0.001, FDR-corrected P = 0.003), Alzheimer’s disease (OR = 1.029, 95%CI: 1.003 ～ 1.054, P = 0.027, FDR-corrected P = 0.045), and vascular dementia (OR = 1.106, 95%CI: 1.023 ～ 1.197, P = 0.012, FDR-corrected P = 0.029). In the study of the effect of dementia on schizophrenia, no form of dementia assessed in this study was found to be a risk factor for schizophrenia. Conclusion Our findings suggest that schizophrenia may be a risk factor for all-cause dementia, Alzheimer’s disease, and vascular dementia, but no dementia of any kind was found to be a risk factor for schizophrenia. Our study provides insights into the potential genetic relationship between schizophrenia and dementia.